2000
DOI: 10.1021/jf990479i
|View full text |Cite
|
Sign up to set email alerts
|

Early Structural Changes in Myosin Rod upon Heating of Carp Myofibrils

Abstract: Upon heating carp myofibrils at 40 degrees C, the amount of myosin that is soluble and monomeric dropped very quickly, roughly 5 times faster than the ATPase inactivation. This rapid decrease of solubility was well explained by a rapid denaturation of the rod portion as measured by chymotryptic digestibility. Chymotryptic digestion of heated myofibrils in a low-salt medium with EDTA generated a reduced amount of rod and subfragment-1 (S-1). The decrease of S-1 produced from the heated myofibrils was consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 19 publications
5
29
0
Order By: Relevance
“…3 It is also accepted that myosin denaturation in fish meat affects the quality of its final products. 7 By using this method, we found that rod denaturation preceded S-1 denaturation in carp myofibrils. 4 As used in the present case, Ca 2+ -ATPase inactivation has been used widely as an index for myosin denaturation.…”
Section: Introductionmentioning
confidence: 90%
“…3 It is also accepted that myosin denaturation in fish meat affects the quality of its final products. 7 By using this method, we found that rod denaturation preceded S-1 denaturation in carp myofibrils. 4 As used in the present case, Ca 2+ -ATPase inactivation has been used widely as an index for myosin denaturation.…”
Section: Introductionmentioning
confidence: 90%
“…Quick decrease of rod production was accompanied by the production of LMM-like or subgfragment-2-like fragments migrating above actin band as proved with fish myofibrils [8]. The pattern found in Ca-medium was similar to that of carp myofibrils and slow rod denaturation in ED-medium was rather similar to that of pollock myofibrils [9].…”
Section: Discussionmentioning
confidence: 60%
“…We proposed that chymotryptic digestion of myofibrils detects myosin denaturation at rod portion as well as head region by their decreased production [8].…”
Section: Introductionmentioning
confidence: 99%
“…Increased digestibility of myofibrils upon heating was the consequence of the exposure of new cleavage sites on myosin molecule to cystein-and serine-types as observed in chymotryptic digestion of heated myofibrils [17]. However, the same structural change of myosin did not expose new cleavage sites for metallo-type, and rather suppressed.…”
Section: Discussionmentioning
confidence: 87%